Shoor in the traditional culture of Tuvans in China - Yusha, Zhanna M. (The New Research of Tuva, 2014)
Article analyzes the folklore (verbal tales genre) of Tuvans in China about the instrumental tunes performed of "shoor” musical instrument.
Keywords: Tuvan folklore; Tuvans in China; Xinjiang Uyghur Autonomous Region; verbal tales; shoor; text semantics; verbal component of tunes